PERANCANGAN DAN PEMBUATAN MESIN PEMOTONG PADI SEDERHANA DI DESA PITALAH KABUPATEN TANAH DATAR - Oknovia Susanti; Bima Sugesti Arif (LPPM Universitas Andalas, 2020)
This activities discusses the design and manufacture of a simple rice cutting machine, while its benefits are useful for helping farmers during the harvesting process who have been using sickles as traditional rice cutting tools. A simple rice mower consists of several components, namely the main frame, a 40T blade, a thrower, Yasui YSI-328 lawn mower, and wheels. The design for the main frame uses Galvanized iron with a size of 1 inch, the specification of the Yasui YSI-328 lawn mower is a 2-stroke engine with a capacity of 1.8 HP 7000 rpm, a blade diameter of 40 T is 255 mm, a rice thrower component is useful for arranging rice so that lying sideways after cutting aims to prevent the rice from being stepped on by the next tools and components, to make it easier for the tools to walk under the Artco wheel. Supporting applications in making product design using Solidworks 2014 software so that an image of the product is obtained. The fabrication process is carried out in the workshop until the tool is ready in a form that matches the design in the image. After the tool is complete, the next step is the testing phase. The testing phase is carried out in the rice field. The parameters to be observed are the working capacity when cutting the variation of rpm and fuel consumption. The average value of the working capacity of a simple rice cutting machine during the experiment is 0.0131 ha / hour; 0.0141 ha / hour; 0.0149 ha / hour at each variation of engine rpm, namely 1900 rpm, 3700 rpm and 5000 rpm. While the average working capacity using traditional sickles is 0.0105 ha / hour. The exhausted fuel consumption at variations of 1900 rpm, 3700 rpm and 5000 rpm respectively is 15.3333 l / ha; 14 l / ha and 12.6667 l / ha.